If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -2 = -12 Reorder the terms: -2 + y = -12 Solving -2 + y = -12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + y = -12 + 2 Combine like terms: -2 + 2 = 0 0 + y = -12 + 2 y = -12 + 2 Combine like terms: -12 + 2 = -10 y = -10 Simplifying y = -10
| -3x+4(2.5)=40 | | 4(3z+4)+3(2z-3)=61 | | bx+b=0 | | 2(t+3)+9(2t-1)=19(t-1)-5 | | 4(3y+2)+5(2y+3)=111 | | -3=3x+7 | | (x-4)6=18 | | -3(3x+2)=2x+6 | | z^2-11z-12= | | 9x-4(3)=-30 | | 5+8n=13+6n | | 4x+12=-9x-53 | | 4(3y+2)+5(2y+3)=11 | | 10+17=3n | | 13x=-65 | | 2(-3)-5y=19 | | 5n+7=32 | | 5w+6y= | | 2(w+9)-(9+5w)=-4w | | (n-10)*3=12 | | ax-x=0 | | 6y+13=14y-11 | | (3z+5)/7=5 | | x+4/6=x-2/4 | | -3-2(x+5)=3(-x-1) | | 4y^2+2y-3=0 | | 141-6x=21x+21 | | 6p-6q= | | -7(n+1)=-8n | | 9(x-5)=-(x-2)+x-11 | | x+(1/3)=1/2 | | (1/3)x+4=(3/4)x-6 |